35 YEARS OF BRAZILIAN CONSTITUTION: CONSTITUTIONAL AMENDMENT No. 115/2022 AND THE IMPORTANCE OF PROTECTING PERSONAL DATA AS A FUNDAMENTAL RIGHT - Silva, Lucas Gonçalves da; Nascimento, Reginaldo Felix; Silva , Lívia Nayara Rocha da (Revista do Programa de Pós-Graduação em Direito, 2024)
This work should be considered a panoramic work, which establishes the process of evolution of the Fundamental Right to the Protection of Personal Data in Brazil, taking as a starting point the Constitution of the Federative Republic of Brazil of 1988, until its formalization as a Fundamental Right Autonomous and Express through Constitutional Amendment No. 115/2022. Furthermore, the work addresses the social and economic aspects that demonstrate the context and importance of having the protection of personal data as a Fundamental Right, which binds all agents in society. Finally, the work addresses the infraconstitutional peculiarities of personal data protection in Brazil, to demonstrate how this Fundamental Right behaves outside the constitutional text. The method used was hypothetical-deductive, using bibliographic and documentary resources. Finally, the Fundamental Right to the Protection of Personal Data functions as a very important right to protect subjects in private relationships, so that it is possible to affirm, in the 35 years since the Constitution of the Federative Republic of Brazil of 1988, that the constitutional text remains compromised with the preservation of the axiom of the Dignity of the Human Person and in providing answers to the social and economic dilemmas experienced by society.